2010
DOI: 10.1080/08003831.2010.527531
|View full text |Cite
|
Sign up to set email alerts
|

Placing Identity: Town, Land, and Authenticity in Nunavut, Canada

Abstract: Recent demographic changes have made settlement patterns in the Canadian Arctic increasingly urban. Iqaluit, capital of Canada's newest territory, Nunavut, is home to the largest concentration of Inuit and non-Inuit populations in the Canadian North. Despite these trends, Inuit cultural identity continues to rest heavily on the perception that to learn how to be authentically Inuit (or to be a better person), a person needs to spend time out on the land (and sea) hunting, fishing, trapping, and camping. Many I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 11 publications
(6 reference statements)
1
35
0
Order By: Relevance
“…Equally, research has indicated that social networks through which traditional foods are shared between and within households are often weaker in RICs, a function of demographics, predominance of livelihoods based on the waged economy, in-migration and transiency in habitation [47-49]. Moreover, the larger settlements, while increasingly prosperous, have significant pockets of inequality, characterized by high and persistent unemployment, poverty, and house overcrowding [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, research has indicated that social networks through which traditional foods are shared between and within households are often weaker in RICs, a function of demographics, predominance of livelihoods based on the waged economy, in-migration and transiency in habitation [47-49]. Moreover, the larger settlements, while increasingly prosperous, have significant pockets of inequality, characterized by high and persistent unemployment, poverty, and house overcrowding [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Many Indigenous groups in Canada have been reclaiming traditional practices, relearning land and hunting skills, and revitalizing Indigenous languages in the wake of the colonial experience (Corntassel, Chaw-win-is, & T'lakwadzi, 2009;Pauktuutit, 2012;Qikiqtani Inuit Association, 2010;Truth and Reconciliation Commission of Canada, 2012). Time on the land has been incorporated into healing programs for adults and youth struggling with substance misuse, trauma, incarceration, and the effects of collective/intergenerational trauma (Berman, 2009;Brady, 1995;Dorais, 2005;Lyons, 2010;Robbins & Dewar, 2011;Searles, 2001Searles, , 2010. The power nuna (land) holds for Nunavummiut is enriching and healing.…”
Section: Literature Review and Consultationsmentioning
confidence: 99%
“…Various studies support land-based programs and the incorporation of time on the land for healing and reconnecting with one's Indigenous heritage (Ilisaqsivik, 2010a(Ilisaqsivik, , 2010bSearles, 2010;Takano, 2005;Tierney, 2007;Wilson, 2003). Many Indigenous groups in Canada have been reclaiming traditional practices, relearning land and hunting skills, and revitalizing Indigenous languages in the wake of the colonial experience (Corntassel, Chaw-win-is, & T'lakwadzi, 2009;Pauktuutit, 2012;Qikiqtani Inuit Association, 2010;Truth and Reconciliation Commission of Canada, 2012).…”
Section: Literature Review and Consultationsmentioning
confidence: 99%
See 1 more Smart Citation
“…What does it mean to be Inuit today? Ned Searles (2001Searles ( , 2002Searles ( , 2006Searles ( , 2008Searles ( , 2010 through his extensive ethnographic work discusses the dialectics between modernity and tradition. He attempts to identify the components or main features of Inuit-ness, so to speak.…”
Section: From the Inuit's 'Traditional' Way-of-life To 'Modernity'mentioning
confidence: 99%